PENINGKATAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL KOOPERATIF TIPE STAD PADA PEMBELAJARAN ILMU PENGETAHUAN SOSIAL KELAS V - Juliyatno, Arwin Dwi; Asran, Mastar; Rosnita, Rosnita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrackA common problem in this research is whether using STAD type co-operative model can improve the learning outcomes of grade V students of Elementary School Negeri 9 Pontianak Tenggara. General purpose in this research is to improve student learning outcomes by using STAD type V cooperative model.This research uses descriptive method with class action research form, and collaborative characteristic. The place of research took place at State Elementary School 09 Pontianak Southeast with the subject of research that is class V which amounted to 30 people. Data collecting techniques used are direct observation techniques and measurement techniques.The collected data is analyzed by calculation of average and percentage. This research was conducted as many as three cycles with 1 meeting in each cycle. The results obtained are 1) the ability of teachers in planning learning in cycle I obtained average score 3.16, cycle II obtained average score 3.45, cycle III obtained average score 3.57. 2) the ability of teachers to implement learning in cycle I obtained average score 3.25, cycle II obtained average score 3.42, cycle III obtained average score 3.69. 3) Students' learning outcomes in the first cycle obtained an average of 74.33 in either category, cycle II obtained average 87.33 in very good category and cycle III obtained average of 93,16 in very good category. The conclusion of data analysis obtained, this shows that the use of STAD type cooperative model can improve student learning outcomes using STAD type cooperative modelÂ Keywords : STAD type cooperative model, social science